Induced Spawning of Giant Gouramy Osphronemus gouramy Lac. by Ovaprim - H. Arfah; L. Maftucha; O. Carman (Jurnal Akuakultur Indonesia)
Spawning season of giant gouramy Osphronemus gouramy Lac is not happen continuously through the year so the supply of fry is not enough for fulfilling the demand.  Artificial fertilization will be useful to produce larvae and fry at out of their spawning season.  In this study, three dose levels of ovaprim, i.e. 0.6, 0.7 and 0.8 ml/kg fish were used to induce spawning of giant gouramy.  Parameters observed were the width of abdomen, number of eggs, fertilization rate, hatching rate, and survival rate of larvae.  The results of this study showed that average of fertilization rate reached 4.3% with number of eggs fertilized was 50 eggs, hatching rate 78.5% with number of larvae hatched was 43 larvas.   Average of larvae survived until the end of experiment was 35, with average survival rate was 76.82%.  Based on the achievement in this study, induced spawning by ovaprim could be applied to giant gouramy, although the success is still very low.